In vitro and in vivo characterisation of the profibrinolytic effect of an inhibitory anti-rat TAFI nanobody - Hendrickx, Maarten L. V.; Zatloukalova, Monika; Hassanzadeh-Ghassabeh, Gholamreza; Muyldermans, Serge; Gils, Ann; Declerck, Paul J. (Thrombosis and Haemostasis, 2014)
One of the main disadvantages of current t-PA thrombolytic treatment is the increased bleeding risk. Upon activation, thrombin activatable fibrinolysis inhibitor (TAFI) is a very powerful antifibrinolytic enzyme. Therefore, co-administration of a TAFI inhibitor during thrombolysis could reduce the required t-PA dose without compromising the thrombolytic efficacy. In this study we generated and characterised a nanobody that is inhibitory towards rat TAFI and evaluated its profibrinolytic property in vitro and in vivo. Nanobody VHH-rTAFI-i81 inhibits (at a 16-fold molar ratio nanobody over TAFI) the thrombin/thrombomodulin (T/TM)-mediated activation of rat TAFI (rTAFI) by 83 ± 1.8% with an IC50 of 0.46 (molar ratio nanobody over TAFI). The affinity (KA) of VHH-rTAFI-i81 for rTAFI, as determined by surface plasmon resonance (Biacore®), is 2.5 ± 0.2 × 1010 M−1 and illustrates a very strong binding. In an in vitro clot lysis assay, administration of VHH-rTAFI-i81 strongly enhances the degree of lysis and reduces time to reach full lysis of t-PA-mediated clot lysis. Epitope mapping discloses that Lys392 is of primary importance for the nanobody/rTAFI interaction besides minor contributions of Tyr175 and Glu183. In vivo application of VHH-rTAFI-i81 in a tissue factor-induced mouse thromboembolism model significantly decreases fibrin deposition in the lungs in the absence of exogenous administered t-PA. Nanobody VHH-rTAFI-i81 is a very potent inhibitor of T/TM-mediated TAFI activation. Co-administration of this nanobody and t-PA enhances the fibrinolytic efficacy. In an in vivo mouse thromboembolism model, VHH-rTAFI-i81 reduces fibrin deposition in the lungs.
Keywords: TAFI; nanobody; fibrinolysis; TAFI inhibition; profibrinolytic; thromboembolism